Investigation of the effects of the detachable vortex generators series on phase change material behavior in an energy storage system. (15th July 2022) - Jalalian Larki, Amrollah; Ghafouri, Ashkan; Assareh, Ehsanolah; Moravej, Mojtaba
Abstract: This study numerically investigated the thermal behavior of an energy storage system, considering different working conditions of the system in both laminar and turbulent flows using a finite volume code. In this regard, three-dimensional numerical simulations were performed using the enthalpy porosity technique to understand the melting dynamics of phase change material. The results were initially compared with available experimental data, revealing that the numerical method was highly accurate when the Mushy coefficient was set to 10 5 . Further, the numerical simulations were extended to study the effects of a series of detachable vortex generators as turbulators on phase change material structures. The main advantage of the series of detachable turbulators was the ability to separate and prevent the accumulation of sediment. According to the results, the case with a series of detachable vortex generators decreased the thermal boundary layer and increased the rate of heat transfer flow by 30% in comparison with a simple system at the same time. Furthermore, at a specific time, the liquid zone for systems with VGs is bigger than that of a simple system by 27%. Finally, the results showed that using a series of detachable vortex generators sped up the melting process by 44%. Highlights: An energy storage system was tested to see how the detachable vortex generators changed the behavior of phase change materials in the system. Using a series of detachable vortex generators sped up the melting process by 44%. The vortex generator system expanded the high temperature and melted zones in the PCM unit faster, compared to the case without a vortex generator system.